Study guides

Q: 9(x plus 3) plus 2(x plus 1)?

Write your answer...

Submit

Related questions

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

2x2+9x+9 = (2x+3)(x+3) when factored

5x + 3 - 4 + 4x = 9x -1

(2x+3)(x+3)

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7

(2x+3)(x+3)

- 7x + (9x - 3) = - 7x + 9x - 3 = 2x - 3

2x+3=9x 3=9x-2x 3=7x x=3/7

2x+3=9x =>3=7x =>3/7=x

9x - 3(x + 13y) = 9x - 3x - 39y = 6x - 39y = 3(2x - 13y)

9x plus 3 plus 2x plus 1 will result to 11x+4(first collect the like terms).

Presumably you want to know the value of x 2x + 3 = 9x 3 = 9x - 2x 3 = 7x 3/7 = x So x = 3/7

khjgfsddfghjfghjk

2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x

X= -2

2x+3=9x-2x -2x3=7x/7 /73/7=x

3(2x - 3)(x + 3)

if you meant: (-3)x²-5x+1=8x²-2x-9x=(±√(449)-3)/22 ≈ -0.1363636363636 ± 1.9263291000379x1=(√(449)-3)/22 ≈ 0.8268009136553x2=(-√(449)-3)/22 ≈ -1.0995281863826

Divide all terms by 3 and it is: (2x-1)(x+2)

3(x + 1)(2x + 1)

You can only add or subtract like terms. So, you subtract 9x from 2x, which gives you -7x. Then subtract -9 from 3 to get -6. And you are left with -7x -6.

2x+5=11 2x=6 x=3

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

2x + 3 = 9x start by bringing the 2x over- minus it from both sides 3 = 7x divide 7 by on sides x= 3/7 x = .4285714285714 repeating.

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2